FORMULASI LOSION EKSTRAK DAUN SALAM (Syzygium polyanthum) SEBAGAI REPELLENT TERHADAP NYAMUK Aedes aegypti - Nopiansyah Nopiansyah; Elia Agustiana (JFL : Jurnal Farmasi Lampung, 2023)
ABSTRACT  Bay leaf is part of the bay plant that contains potentially terpenoid compounds as mosquito's natural repellent. The purpose of this study was to determine the formula composition and effectiveness of repellent n-hexane bay lotion extract with concentrations of 0%, 40%, 50, and 60%. This research is an experimental research. The making of bay leaf extract is used by maceration method. Lotion is made in 4 formulas on the basis of nonionic formula namely FI with extract concentration of 0%, FII with extract concentration of 40%, FIII extract concentration of 50% and FIV with extract concentration of 60%. The results of the non-specific parameter test obtained 2.9% water content, total ash content of 5% and acid insoluble ash content of 0.6% then proceed with organoleptic test, homogeneity, pH, centrifugation, dispersion, viscosity and cycling test. Repellent activity testing is done by counting the number of mosquitoes that alight and not, the average percentage of repellent power of Aedes aegypti at a concentration of 40% is 65.3%, at a concentration of 50% that is 78.6%, and at a concentration of 60% that is 90 8%, the most effective is 60% concentration. From the results of the Anova One Way test, the value of p was 0,000 ≤ 0.05 so it was proven that there were differences in various concentrations of bay leaf extract as repellent to Aedes aegypti mosquitoes. The results of this study indicate that bay leaf extract can be made in a nonionic-based lotion lotion with various concentrations. The physical properties of lotion preparations with variations in bay leaf extract levels did not affect the physical stability of the lotion and did not change during testing and had the effectiveness of mosquito repellent.  Keywords: Aedes Aegypti, N-Hexane,  Repellent, Salam Leaf Extract